Level of physical activity, body mass index (BMI), and sleep patterns in junior and senior high school students of Kediri city and regency - Sugito; Allsabah, Muhammad Akbar Husein; Trio Kurniawan, Bambang (Journal Sport Area, 2022)
During the current pandemic, the pattern of activity, lifestyle, and sleep quality of students at the school level has changed due to the Covid 19 outbreak which required students to reduce their activities outside the home. The purpose of this study was to find out the level of physical activity, body mass index (BMI), and sleep patterns Junior High School (SMP) and Senior High School (SMA) students of Kediri City and District. This study uses quantitative qualitatively described methods. The subjects of this study are 548 participants of the Junior High School (SMP) and Senior High School (SMA) in Kediri City and District. Instruments in this study for physical activity levels use IPAQ (International Physical Activity Quessionare) questionnaires, body mass indexes using BMI questionnaires, and sleep patterns using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The results of this study show that physical activity levels of 81% fall into the Moderate category, Body Mass Index by 63% falls into the Normal category, and sleep patterns by 83% fall into the bad category. The results of this study have limitations on certain levels of education and a limited number of samples who perform new habits due to the Covid-19 pandemic. The results of this study show the real impact of the Covid-19 pandemic for school students, so in the future there needs to be a research study that can overcome the impact of the pandemic on students, namely regarding health and lifestyle.